Relation between frost tolerance and post-cryogenic recovery in Hypericum spp - Petijova, L; Brunakova, K; Zámečník, Jiří; Zubricka, D; Misianikova, A; Kimakova, K; Cellarova, E (Cryo-letters, 2014)
BACKGROUND: The species of the Hypericum genus are markedly variable in morphological, physiological and biochemical traits. They significantly differ in their area of distribution, which may determine their natural tolerance to environmental conditions, such as temperature extremes. OBJECTIVE: To test the hypothesis that the species growing worldwide in different regions and altitudes would be better able to withstand cryopreservation than the endemics. METHODS: The frost tolerance of 10 selected Hypericum species was evaluated. A possible stimulatory effect of cold-acclimation and vitrification-associated stressors on the content of hypericins was also investigated RESULTS: We found that frost tolerance of 10 selected Hypericum species expressed by LT50 ranged between -11 degree C for the species occurring worldwide and -4 degree C for sub/tropical frost sensitive taxons which corresponded with their natural habitats. CONCLUSIONS: Although the mean recoveries for all species cryopreserved with the same vitrification procedure did not exceed 30%, the effect of genetic predisposition to cold tolerance should be considered for optimisation of cryopreservation protocol. Our data neither proved an elicitation effect of cold on hypericin biosynthesis, nor correlation between hypericin content and quantitative characteristics of the hypericin-accumulating black nodules.
Keywords: druhová specificita; třezalka; aklimatizace; Cryopreservation; Hypericum; kryoprezervace; nadmořská výška; nízká teplota; Cold Temperature; Species Specificity; Altitude; Acclimatization